A new species of Lonchodryinus (Hymenoptera, Dryinidae) from Upper Eocene Baltic amber - Olmi, Massimo; Vasilenko, Dmitry V.; Capradossi, Leonardo; Perkovsky, Evgeny E.; Guglielmino, Adalgisa (Zootaxa, 2021)
Lonchodryinus groehni sp. nov. (Hymenoptera: Chrysidoidea: Dryinidae) is described from Baltic amber. The new species is close to L. balticus Olmi & Guglielmino, 2012, but it can be distinguished for the different OPL/POL ratio and 2r-rs&Rs vein of the fore wing. A key to the fossil species of Lonchodryinus and a comparison with the extant species L. ruficornis (Dalman, 1818) are presented.